Hadist Tematik Ilmu Ghaib - Mohamad Hambali; Muhammad Alif (PT. AHLAL PUBLISHER NUSANTARA, 2025)
In the structure of Islamic belief, the understanding of the unseen (al-ghayb) plays a crucial role as a divider between the absolute power of God and the limitations of His creatures. Nevertheless, social phenomena showing reliance on future predictions and occult practices indicate the existence of theological confusion within society. This study aims to re-map the parameters of the validity of knowledge about the unseen by applying a thematic (maudhu’i) approach to hadith literature. The primary data sources focus on authoritative narrations in Sahih al-Bukhari and Sahih Muslim that discuss the demarcation between divine and worldly knowledge.The examination of these hadith texts reveals three fundamental principles. First, the aspect of divine exclusivity: the five keys to the unseen (such as the time of death and the Day of Judgment) are a closed domain inaccessible to anyone except Allah. Second, the prophetic boundary: it affirms that the Prophet Muhammad’s knowledge of the unseen is not an inherent capability, but rather derivative information granted through revelation as proof of prophethood. Third, the mechanism of faith protection: Islam closes the door to polytheism by prohibiting astrology and sorcery, and by defining fortune-telling as distorted information stolen by jinn entities.In conclusion, the validity of a believer’s faith is measured by their rejection of mystical speculation and their total submission to the authority of revelation in responding to future mysteries. Keywords: Islamic Theology, Thematic Hadith, Limits of Revelation, The Unseen, Monotheism. Abstrak Dalam struktur keyakinan Islam, pemahaman mengenai entitas yang tak terindra (al-ghayb) memegang peranan krusial sebagai pemisah antara kekuasaan mutlak Tuhan dan keterbatasan makhluk. Kendati demikian, fenomena sosial yang menunjukkan ketergantungan pada ramalan masa depan dan praktik klenik mengindikasikan adanya kerancuan pemahaman akidah di masyarakat. Penelitian ini bertujuan untuk memetakan kembali parameter validitas pengetahuan ghaib dengan menerapkan metode tematik (maudhu’i) pada literatur hadis. Sumber data primer difokuskan pada riwayat-riwayat otoritatif dalam Shahih al-Bukhari dan Shahih Muslim yang membahas demarkasi pengetahuan langit dan bumi.Hasil penelusuran terhadap teks-teks hadis menemukan tiga prinsip fundamental. Pertama, aspek eksklusivitas ketuhanan: di mana lima kunci rahasia ghaib (seperti waktu kematian dan kiamat) adalah domain tertutup yang tidak terjangkau oleh siapa pun selain Allah. Kedua, batasan kenabian: yang menegaskan bahwa pengetahuan Rasulullah SAW mengenai hal ghaib bukanlah kemampuan inheren, melainkan informasi derivatif yang bersumber dari wahyu sebagai bukti kerasulan. Ketiga, mekanisme perlindungan iman: Islam menutup celah kesyirikan dengan mengharamkan astrologi dan perdukunan, serta mendefinisikan ramalan sebagai distorsi informasi yang dicuri oleh entitas jin. Kesimpulannya, validitas iman seorang mukmin diukur dari penolakannya terhadap spekulasi mistis dan kepasrahannya total pada otoritas wahyu dalam menyikapi misteri masa depan. Kata kunci: Teologi Islam, Hadis Tematik, Batasan Wahyu, Kegaiban, Tauhid.